Early Intracranial Hemorrhage Predicts Poor Clinical Outcome in Community-Acquired Bacterial Meningitis - Weller, Johannes; Enkirch, Jonas Simon; Lehmann, Felix; Radbruch, Alexander; Klockgether, Thomas; Zimmermann, Julian (Frontiers in Neurology, 2022)
Background Community-acquired bacterial meningitis in adults is associated with significant morbidity and mortality; therefore, early prognostication is important to identify severe cases and possibly allocate more intensive treatment. We hypothesized that early intracranial hemorrhage portends a poor prognosis. The objective of this study was to evaluate the prognostic impact of early intracranial hemorrhage regardless of size and location on clinical outcome. Methods Retrospective analysis of patients with community-acquired bacterial meningitis treated at a tertiary academic center between 2009 and 2019 about patient characteristics, cerebral imaging findings, and clinical outcome. Uni- and multivariable logistic regression analyses were performed to identify independent predictors of poor clinical outcomes defined as a modified Rankin scale score of 5 or 6 upon discharge. Results A total of 102 patients were included, of which 22.5% had poor clinical outcomes. Intracranial micro- or macrohemorrhages were present in 7.8% of cases and associated with poor clinical outcomes [odds ratio (OR) 55.75, 95% CI 3.08–1,008.48, p = 0.006] in multivariate analysis, further predictors included ischemic stroke (OR 15.06, 95% CI 1.32–172, p = 0.029), age (OR 2.56, 95% CI 1.4–4.67, p = 0.002), and reduced consciousness (OR 4.21, 95% CI 1.07–16.64, p = 0.04). Conclusion Early cerebral hemorrhage (ECHO) is a potential prognostic marker for clinicians confronted with decision-making in patients who are critically ill with community-acquired bacterial meningitis.